STUDI KUALITAS IKAN KEMBUNG (Rastrelliger sp.) SECARA ORGANOLEPTIK YANG DIJUAL DI PASAR TRADISIONAL KOTA SERANG - Nunung Rohani, - (2023)
ABSTRACT The level of freshness of fish plays a very important role in determining the quality of fish. Banten Province is a producing area for marine fisheries reaching 5,248,933 kilograms per year. Serang City obtained the highest fish production with a total of 6.2 million kilograms or a percentage of 42.02% in 2020. The most widely sold type of fish at TPI Serang City is mackerel (Rastrelliger sp.). The purpose of this study was to determine the organoleptic quality of fish marketed in Serang City. The research will be conducted in February 2023 in 4 markets in Serang City, namely Lama Market, Rau, Karangantu, and Kalodran. The method used is a survey method by directly observing the activities of traders starting from the beginning of sales to 1 hour after. Sampling was carried out on mackerel species, then 3 randomly taken fishtails. Organoleptic assessment and microbial tests were carried out at 07.00 until completion. The results of organoleptic assessment were analyzed using the Wallis Kruskal Test and Post-hoc test at a confidence level of 95% (p < 0.05) then tested LSD (Least Significant Difference). The results showed that the mackerel species tested in four Serang City markets were mostly fresh because referring to SNI (2729-2013) that fish assessment was still qualified with results of more than >7 and above (p < 0.05) Cfu / ml. Keywords : fish, quality, market, organoleptic, microbial